Optimalisasi Penggunaan Sensor Pada Sistem Penyiraman Tanaman Kangkung Menggunakan Metode WSN - Patriana, Ari; Arip, Arip; Fauzi, Willy Muhammad (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
Water spinach is one of the agricultural products that is often consumed by Indonesian people, so it has very high market demand. However, there are still many farmers who use the traditional method of watering plants by carrying water so that it does not increase plant productivity. This is also a problem because farmers are at risk of developing MSDs (musculoskeletal disorders). To support high market demand, technology is needed that can help farmers in the process of watering plants with high effectiveness and efficiency. In this research, optimization of the use of sensors was carried out using WSN (Wireless Sensor Network) to overcome the problem of increasing scale on large areas of land to be able to monitor park land and control the watering process. This system uses several sensors, including a water pressure sensor, waterflow sensor, soil pH sensor and soil moisture sensor. Apart from that, this research also created a warning system and recommendation system to help farmers in making decisions regarding plantation management. Farmers can monitor garden land and control watering from anywhere via the web application that has been created